Impact of microwave irradiation on the properties of the manganese oxide based electrode materials for lithium-ion and sodium-ion batteries - Nkosi, Funeka Phumzile (My University, 2018)
This work involved the study of manganese oxide based materials as cathode materials in lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs). A lithium manganese richtransition metal oxide, Li1.2Mn0.52Co0.13Ni0.13Al0.02O2 (LMNCA) cathode material was successfully prepared using the combustion method. Urea and ethylene glycol (EG) were used as fuels during the combustion synthesis and their effect on the physical and electrochemical properties of the samples were evaluated. This study revealed that the combustion synthesis of electrode materials depends greatly on the type of fuel to produce materials with enhanced electrochemical properties. LMNCA prepared by urea (LMNCA-urea) delivered the higher specific capacity of 295 mAhg with a capacity retention of 84 percent after 50 cycles, while the LMNCA prepared by EG (LMNCA-EG) gave a capacity of 240 mAhg and a capacity retention of 78 percent after 50 cycles. Even though LMNCA-urea has enhanced cycle performance, it has higher voltage fade and decomposition of electrolyte occurs upon cycling as compared to LMNCA-EG. The effect of microwave irradiation on the combustion synthesis of LMNCA using either the urea or EG was also studied. The microwave irradiation improved the capacity and the rate capability of LMNCA-EG by decreasing the particle size and tuning the oxidation state of the manganese ion content. The capacity retention after 50 cycles at 0.1 C is 88 percent and 82 percent for LMNCA-EG and LMNCA-urea, respectively. The XRD analysis revealed pure, crystalline LMNCA powders with good hexagonal ordering. The SEM images showed that LMNCA powders exhibited plate-like particles with smooth surfaces, an unusual morphology for LMNCA materials. The LMNCA material exhibited excellent cycle performance and good rate capability. The capacity retention was 95 percent and 96 percent after the 50th and 100th cycles, respectively. The preparation of P2-type Na0.67Mg0.28Mn0.72O2 (NaMgMnO) cathode materials for sodium-ion batteries using a urea combustion method is also reported for the first time. The effect of microwave irradiation and fluorination was investigated with the aim to improve the capacity retention and the rate capability of NaMgMnO cathode material. The powder XRD analyses showed that pure single phase P2-type powders were successfully prepared. SEM analyses revealed an impact of microwave irradiation and fluorination on the morphology of the materials. The galvanostatic charge-discharge and the electrochemical impedance spectroscopy studies showed that both microwave irradiation and fluorination improved the capacity, coulombic efficiency, cycle performance and impedance of NaMgMnO cathode materials.
A Thesis submitted for the faculty of Science at the University of Witwatersrand Johannesburg, in the fulfilment for the degree of Doctor of Philosophy in Chemistry, 2018
Keywords: Lithium-ion batteries--Materials; Organic compounds--Synthesis